Electrical characterization of electronic circuits produced by inkjet printing - Parkula, Vitaliy (2016)
Dissertação de Mestrado, Engenharia Electrónica e Telecomunicações, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2014